Cultural Criminology? Cultural Anthropology and the Study of Homicide in Anglo-Saxon Countries (Archives of Criminology, 2006)
The paper covers the issue of cultural and ethnological perspective in contemporary criminology. The author presents various theories that are currently developing worldwide, addressing the problem of the role of culture (in the anthropological sense of the word) and its influence on the aetiology of criminal behaviour, social reaction to crime, and creation of role-modelling in different societies. The presentation is focussed mostly on the cultural and criminological comparison of three countries the United States of America, Great Britain and Canada – and their homicide data. These countries, although seemingly similar in many ways when traditionally analysed in criminology, differ significantly in terms of murder – not only statistically, but also at a deeper and more complex historical level. The author describes these differences, arguing that the cultural approach to criminological issues is crucial in explaining violence. The last part of the paper focuses on case-study examples from all the three countries under discussion; this serves as an illustration to the author’s postulate of incorporating the ethnological studies and research into the system of criminology.